Acceptor Interlocked Molecular Design for Solution‐Processed Stable Deep‐Blue TADF and Hyper Fluorescence Organic LED Enabling High‐Efficiency. Issue 18 (3rd July 2022) - Alam, Md Intekhab; Nagar, Mangey Ram; Nayak, Sandhya Rani; Choudhury, A.; Jou, Jwo‐Huei; Vaidyanathan, Sivakumar
Abstract: Solution processed deep‐blue organic light emitting diodes (OLEDs) with high external quantum efficiency (EQE) and a long operational lifetime are still constrained. In this context, two thermally activated delayed fluorescence (TADF) emitters are synthesized utilizing a new design strategy of twisted interlocked acceptor core integrated with carbazole (KCCz) and tert‐butylcarbazole (KCTBC) as donors, respectively, for solution processed deep‐blue TADF OLEDs. Twisting of the acceptor core by two methyl groups results in complete separation of highest occupied molecular orbital and lowest unoccupied molecular orbital, along with cyanide group facilitating the generation of low‐lying triplet excited states as suggested by theoretical simulation. The combined effect of both results in tuning of emission in ultradeep blue region through the efficient population of triplet excitons and concurrently reverse intersystem crossing to produce highly efficient devices. A doped device based on KCTBC shows EQEmax of 9.0% along with low efficiency roll‐off with long operational device half lifetime of 72 min at initial brightness of 1000 cd m −2, and Commission Internationale de L'Eclairage (CIE) coordinates of (0.17, 0.13). In addition, with 12.5 wt% of 4CzFCN as assistant dopant/cohost the performance of the KCTBC‐based device is enhanced to an EQEmax of 13.9% and CIE coordinates of (0.18, 0.13). Further, a high‐efficiency warm white OLED adopting the TADF hybrid approach is realized with EQEmax of 9.0%. Abstract : Twisted interlocked acceptor core‐based thermally activated delayed fluorescence (TADF) molecules are designed and synthesized for solution‐processed deep‐blue organic light emitting diodes (OLEDs). A KCTBC‐based doped device shows 9.0% maximum external quantum efficiency (EQEmax ), with CIE (0.17, 0.13). 4CzFCN as an assistant dopant boosts the performance of the KCTBC‐based hyperfluorescent deep‐blue device with an EQEmax of 13.9%. A high‐efficiency warm white OLED using the TADF hybrid method achieves 9.0% EQEmax .